Melatonin promotes cardiomyogenesis of embryonic stem cells via inhibition of HIF-1α stabilization - Kudová, Jana; Vašíček, Ondřej; Číž, Milan; Kubala, Lukáš (Journal of pineal research, 2016)
Melatonin, a molecule involved in the regulation of circadian rhythms, has protective effects against myocardial injuries. However, its capability to regulate the maturation of cardiac progenitor cells is unclear. Recently, several studies have shown that melatonin inhibits the stabilization of hypoxia-inducible factors (HIFs), important signaling molecules with cardioprotective effects. In this study, by employing differentiating mouse embryonic stem cells, we report that melatonin significantly upregulated the expression of cardiac cell-specific markers (myosin heavy chains six and seven) as well as the percentage of myosin heavy chain-positive cells. Importantly, melatonin decreased HIF-1α stabilization and transcriptional activity and, in contrast, induced HIF-2α stabilization. Interestingly, the deletion of HIF-1α completely inhibited the pro-cardiomyogenic effect of melatonin as well as the melatonin-mediated HIF-2α stabilization. Moreover, melatonin increased Sirt-1 levels in a HIF-1α-dependent manner. Taken together, we provide new evidence of a time-specific inhibition of HIF-1α stabilization as an essential feature of melatonin-induced cardiomyogenesis and unexpected different roles of HIF-1α stabilization during various stages of cardiac development. These results uncover new mechanisms underlying the maturation of cardiac progenitor cells and can help in the development of novel strategies for using melatonin in cardiac regeneration therapy.
Keywords: vývoj svalů; Mice; myší embryonální kmenové buňky; Mouse Embryonic Stem Cells; myokard; faktor 1 indukovatelný hypoxií - podjednotka alfa; Melatonin; Animals; Myocardium; Protein Stability; zvířata; myši; stabilita proteinů; Muscle Development; melatonin; Hypoxia-Inducible Factor 1, alpha Subunit